The 25 October 2018 Mw = 6.7 Zakynthos earthquake (Ionian Sea, Greece): A low-angle fault model based on GNSS data, relocated seismicity, small tsunami and implications for the seismic hazard in the west Hellenic Arc. (June 2020) - Ganas, Athanassios; Briole, Pierre; Bozionelos, George; Barberopoulou, Aggeliki; Elias, Panagiotis; Tsironi, Varvara; Valkaniotis, Sotiris; Moshou, Alexandra; Mintourakis, Ioannis
Abstract: We present a joint analysis of seismological and Global Navigation Satellite System (GNSS) data of the seismic sequence that started on October 25, 2018 with a shallow Mw = 6.7 earthquake offshore Zakynthos (Ionian Sea, Greece). The inversion of the GNSS data shows the activation of a N-S striking thrust/oblique-slip fault at the African-Aegean plate interface with a length of ∼26 km, and depth shallower than 15 km. The fault-plane geometry is well constrained by GNSS with a low-dip angle (23°), and dip-direction towards east. This is consistent with the distribution of the relocated aftershocks (1811 events). Our analysis indicates that the October 25, 2018 event ruptured the Hellenic megathrust. This event highlights the high degree of seismic coupling in the western region of the Hellenic Arc. It also highlights the "strong" nature of the subducting slab with the occurrence of "locked" patches under the Ionian seafloor that fail during large, reverse/oblique-slip earthquakes. The latest, shallow seismic events of the western Hellenic arc (1976 Zakynthos, 1997 Strofades, 2018 Zakynthos) point to a sequence of low-angle events along the plate interface with most of co-seismic deformation taken up by the upper (Aegean) plate. The GNSS data also point to a similar pattern between the co-seismic strain release and the long-term (interseismic) strain accumulation along the west Hellenic Arc.